Density and strength distribution of the subchondral bone plate of the canine talus - Vali, Yasamin; Müller-Gerbl, Magdalena; van Bree, Henri; Dingemanse, Walter; Gielen, Ingrid (Frontiers in Veterinary Science, 2025)
IntroductionThe subchondral bone plate plays a critical role in load transfer across joints. Its density distribution reflects the joint’s loading history, and variations in density are likely associated with changes in the material properties of the subchondral bone. This study aimed to evaluate the mechanical strength of the subchondral bone plate of the canine talus and correlate it with the subchondral bone density.MethodsTwenty paired cadaveric tali from large breed dogs were included in the present study. Test points were selected and marked on the subchondral bone plate, where mechanical strength was assessed using indentation testing to record the maximum penetration force. The density at these test points was measured using computed tomographic osteoabsorptiometry (CT-OAM).ResultsThe result revealed that density and strength of the subchondral bone plate were not uniformly distributed across its surface. A strong correlation was observed between subchondral bone density and mechanical strength across all specimens, with the areas of highest density corresponding to the areas of greatest mechanical strength.DiscussionThe present study’s key finding—a strong correlation between subchondral bone density and mechanical strength—highlights the potential of using subchondral bone density as a reliable indicator of mechanical strength. This relationship offers important insights for clinical assessments and research on joint biomechanics. Furthermore, the use of CT-OAM provides a non-invasive method to evaluate both the density and mechanical strength of the subchondral bone plate, enabling valuable longitudinal studies on subchondral bone properties in dogs.